Safer Tractor Operations: Introduction - Carol J. Lehtola; Charles M. Brown (EDIS)
Florida AgSafe, the Florida Agricultural Safety Program, has created a series of publications to be used in training and education in the safer use of tractors. This workbook introduces the series of six comprehensive circulars for different professions and owners. Each of the eight fact sheets focus on one specific area of tractor safety. These publications are ideal for use as the basis of tractor safety programs. They cover many topics related to safer tractor use and include training activities, pre-post tests and record-keeping tools. This document is ABE342, one of a series of the Agricultural and Biological Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 2003.